Assessment of the severity and incidence of Faba bean ascochyta blight (Ascochyta fabae S.) disease in Northwestern Ethiopia. (14th December 2021) - Tessema, Habtu; Sintayehu, Asefa; Alem, Teferi; Teshome, Zewdu
Abstract: Faba bean ( Vicia fabae L .) facing challenges in its production due to lack of appropriate agronomic practices weather uncertainties and diseases outbreaks. Assessment of the severity and incidence of faba bean ascochyta blight ( Ascochyta fabae S.) disease in nine districts of Northwestern Ethiopia was conducted to indicate the distribution, incidence and severity of ascochyta blight disease and its association with agro-ecological factors and agronomic practice. A total of 216 farm fields, 98 and 118 randomly assessed in 2019 and 2020 cropping season's respectively. The associations of the disease intensities with independent variables were analyzed using logistic regression model. The highest mean disease incidence and severity during the survey years were 99.5% and 76.9%, respectively. This indicates that ascochyta blight is a major biotic constraint for faba bean production in the study areas. Therefore, integrated aschochyta blight disease management options should be developed to improve the productivity of the crop in Northwestern Ethiopia.